Desarrollo de una línea de productos gastronómicos a base del aguacate (persea americana) cultivado en el cantón Mira - Cañarejo Pastaz, José Andrés (2021)
The Mira canton has become an important avocado production area and has been very well received in its commercialization at a national and international level. The objective proposed in this work is to develop knowledge of the use of avocado grown in the Mira canton, through a line of gastronomic products that promotes the dynamization of its trade. In order to comply with it, it was based on the research question that was posed in the following way, In what way does the use of avocado grown in the Mira canton influence the development of a line of gastronomic products that promote the dynamization of its trade? Regarding the methodology, it was defined that it is an applied research with a mixed approach, which involves three types of research that are\; documentary, experimental and explanatory\; Two surveys were conducted, one addressed to 68 mireño avocado producers and the other to 163 potential clients, the interviews were conducted with 3 chefs and a food engineer, these techniques and instruments were carried out in order to obtain the necessary information to the elaboration of the line of gastronomic products based on avocado, the data obtained were given during the month of November 2020. The relevant results obtained are the following\; Farmers perceive the need for their product, avocado, to be given a use or transformation in the same locality to later market it, in order to obtain better benefits for the locality, in terms of potential customers it was obtained that there is the lack of knowledge that avocado can give way to different gastronomic products, such as those proposed in this research.